A Systematic Review of the Critical Factors for Success of Mobile Learning in Higher Education (University Students' Perspective). (April 2015) - Alrasheedi, Muasaad; Capretz, Luiz Fernando; Raza, Arif
The phenomenon of the use of a mobile learning (m-Learning) platform in educational institutions is slowly gaining momentum. However, the enthusiasm with which mobile phones have been welcomed into every aspect of our lives is not yet apparent in the educational sector. To understand the reason, it is important to understand user expectations of the system. This article documents a systematic review of existing studies to find the success factors for effective m-Learning. Our systematic review collates results from 30 studies conducted in 17 countries, where 13 critical success factors were found to strongly impact m-Learning implementation. Using these results within the framework of the diffusion of innovation model for innovation adoption and the critical success factors together help us see what aspects of the innovation decision process are the likely causes of the reduced take-up of m-Learning by university students.